O processo de desenvolvimento e legitimação de mercados: o caso da legalização da marijuana no Uruguai - Dias, William Weber (Universidade do Vale do Rio dos Sinos, 2016)
This study intends to understand the process of legitimation of marijuana in Uruguay. For the first time a country legalizes all cannabis market sectors. Based on similar studies as the legitimation of American casinos and the change in the music industry with downloads, the study follows the line of the main studies of legitimation and is based on institutional theory to analyze the market legitimation process . With an exploratory approach, this research began in a process of desk research and analysis of media discourse and its second stage sought inspiration in ethnographic research which were conducted informal interviews, daily field, observations and semi-structured interviews. The process of analysis and data collection took into account all the official players involved in the new market. The results showed a market with changes after the approval of the legalization law. With just over two years of legalized market, there is a certain maturity in the market and competitors by differentiating quality and distribution. About consumers, these have consumption rites and practices established even before legalization, which indicates a legitimisation in previous process change granted by Uruguay's President Pepe Mujica. The study also opens the possibility for other forms of legitimation and discusses with work as a theoretical lens differences and similarities in legitimation. There are complementary opportunities as they were not addressed issues such as drug trafficking and the dangers that this new market can bring to society. The results are interesting for Uruguayan citizens but also for other countries seeking legalization in several markets. Entrepreneurs and dreamers who sometimes dream with the creation of a new market or launching a product.
Keywords: Legitimação de mercado; Legalização da maconha; Novos mercados; Pesquisa exploratória; Market legitimation; Marijuana legalization; New markets; Exploratory research; ACCNPQ::Ciências Sociais Aplicadas::Administração